The Efficacy of Vaginal Suppository Based on Alcea angulata Freyn & Sint. (A Persian Medicine Product) in Patients with Vaginal Atrophy: A Randomized, Double-Blind, Placebo-Controlled Trial - Alieh Kianitalaei; Zohre Feyzabadi; Nasser Behnampour; Shokuhsadat Hamedi; Faride Akhlaghi; Marzieh Qaraaty (Tehran University of Medical Sciences, 2022)
Vaginal atrophy is one of the most common complaints in postmenopausal women. Symptoms of vaginal atrophy include dryness, itching, bleeding, and dyspareunia. According to Traditional Persian Medicine (TPM), the using of moisturizing plants can treat dry mucous membranes. TPM suggests the use of marshmallow (Alcea angulata) to moisturize dry cells with its mucilage. The aim of this study was to evaluate the effect of Alcea on the treatment of vaginal atrophy. This double-blind, clinical trial was conducted on 60 postmenopausal women with vaginal atrophy (40 - 65 years of age). The patients were randomly assigned into two groups of treatment and control (n = 30). The treatment group received Alcea vaginal suppository 5% (125 mg), and the control group received placebo. Both groups used suppositories every night for two weeks and every other night for six weeks. Vaginal Maturation Value (VMV), symptoms of vaginal atrophy, and pH were compared before and after the intervention. Data were analyzed using SPSS 16. VMV was increased in the treatment group, from 40.30  ±13.27 to 46.40 ± 11.27, (p ˂ 0.0001) compared to the control group, in which the change of VMV was not significant (p = 0.122). The vaginal pH was significantly decreased in the treatment group, from 6.45 ± 0.92 to 5.52 ± 0.62, (p ˂ 0.0001) compared to the control group, in which the change of pH was not significant (p ˂ 0.257). The symptoms were significantly reduced in the treatment group. It seems that Alcea vaginal suppository can be useful as a natural product to relieve the symptoms of vaginal atrophy.